Prescription Screening Study for Outpatient Prescribing Administration of Social Security Administrator Patients at Dr R.M Djoelham Regional General Hospital, Binjai City - Pratiwi Rukmana Nasution (Universitas Islam Negeri Sumatera Utara, Medan, 2021)
The Impact of errors in prescription incompleteness is diverse, started from those that do not provide any risk at all to the occurrence of disability or even death. The Prescription screening is useful to prevent omissions information, poor prescribing and inappropriate prescribing. The goal of this study was to screen the completeness of administration of outpatient prescriptions for social security administrator patients in regional public hospital Dr. R.M. Djoelham at Binjai City. This is a observational research with a retrospective descriptive design, and use the purposive sampling. This research was conducted at the General Hospital Pharmacy Installation Dr. R.M. Djoelham City of Binjai. This research was conducted from April-June 2021. The population of this study was the number of patient prescriptions from January 2021 to March 2021, namely 3722 prescriptions. The total sample is 98 recipes.The data analysis used is univariate data analysis. The results of the 98 recipes show the percentage of administration of the Inscriptio reached 68.4% and was incomplete reached 31.6%, on complete Invocatio it reached 100%, on Prescriptio the complete reached 95% and the incomplete reached 5%, the Signatura complete reached 91.84% and incomplete reached 8.16%, on Subscriptio the full one reaches 100%, the complete Pro reaches 58.84% and incomplete reached 41.16%. The conclusion of this study is the percentage of complete recipes reached 67.35% while incomplete reached 32.65%. If an incomplete prescription is found, it is hoped that the pharmacy staff will confirm it with the doctor concerned. Keyword: Pharmaceutical Installation, Prescription Completeness, Screening